2018
DOI: 10.1108/yc-09-2017-00737
|View full text |Cite
|
Sign up to set email alerts
|

Modeling satisfaction and repurchase intentions of mobile smart wristbands: the role of social mindfulness and perceived value

Abstract: Purpose This paper aims to empirically test a model of different facets of perceived value (economic, emotional, aesthetic and convenience) and social mindfulness (SM) as determinants of consumer satisfaction and repurchase intentions of mobile smart wristbands. Design/methodology/approach A questionnaire designed to assess these effects was administered to students at a Midwestern US university. Data were analyzed using AMOS structural equation modeling software. Findings The findings reveal that SM was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
4
14
2
4
Order By: Relevance
“…The strong levels of satisfaction perceived by the high bandwagon individuals are connected to their greater susceptibility to social influences compared to the low bandwagon individuals. This result supports the outcome of previous studies (e.g., Oyedele et al, 2018) about the relevance of social influences in predicting consumer perceptions and satisfaction.…”
Section: Analysis and Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The strong levels of satisfaction perceived by the high bandwagon individuals are connected to their greater susceptibility to social influences compared to the low bandwagon individuals. This result supports the outcome of previous studies (e.g., Oyedele et al, 2018) about the relevance of social influences in predicting consumer perceptions and satisfaction.…”
Section: Analysis and Resultssupporting
confidence: 91%
“…For instance, the findings about perceived value are consistent with previous findings on convenience value (e.g., Collier & Kimes, 2013;Oyedele et al, 2018;Pura, 2005). Specifically, Oyedele et al (2018) found that utilitarian values (e.g., convenience value) significantly affect satisfaction and, subsequently, repurchase intentions. Kim et al's (2013) study showed that the ease of use and perceived value of mobile apps in consumption situations positively impacts customer-engagement and satisfaction with a brand.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Hipotesis 5: Perceived value berpengaruh secara signifikan terhadap repurchase intention memiliki kesamaan dengan penelitian terdahulu yang dilakukan oleh Oyedele et al (2018). Konsumen merasakan manfaat yang menguntungan akan melakukan transaksi kembali dimana konsumen mendapat manfaat yang lebih dari apa yang diminta atau dibayarkan akan muncul kepuasan yang menjadi pengalaman berbelanja.…”
Section: Tabel 4 Hasil Uji Hipotesisunclassified